2019
DOI: 10.3390/biom9100517
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ghrelin Activity by Receptor Antagonist [d-Lys-3] GHRP-6 Attenuates Alcohol-Induced Hepatic Steatosis by Regulating Hepatic Lipid Metabolism

Abstract: Alcoholic steatosis, characterized by an accumulation of triglycerides in hepatocytes, is one of the earliest pathological changes in the progression of alcoholic liver disease. In our previous study, we showed that alcohol-induced increase in serum ghrelin levels impair insulin secretion from pancreatic β-cells. The consequent reduction in the circulating insulin levels promote adipose-derived fatty acid mobilization to ultimately contribute to hepatic steatosis. In this study, we determined whether inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…In correlation with adipocyte size, we observed increased HSL enzyme activity and decreased expression of PPARγ, which induces adipose differentiation and increases its fat storing capacity in the eWAT of ethanol-fed rats compared with control. These ethanolinduced changes in eWAT promote adipose lipolysis, causing a rise in adipose-derived serum NEFA levels as reported in our recent study (Rasineni et al, 2019a). Fasting pair-fed control rats reduced eWAT PPARγ expression while it increased adipose p-HSL levels, thereby enhancing lipolysis, as evident by reduced adipocyte size, and subsequently, an elevation in serum NEFA levels.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In correlation with adipocyte size, we observed increased HSL enzyme activity and decreased expression of PPARγ, which induces adipose differentiation and increases its fat storing capacity in the eWAT of ethanol-fed rats compared with control. These ethanolinduced changes in eWAT promote adipose lipolysis, causing a rise in adipose-derived serum NEFA levels as reported in our recent study (Rasineni et al, 2019a). Fasting pair-fed control rats reduced eWAT PPARγ expression while it increased adipose p-HSL levels, thereby enhancing lipolysis, as evident by reduced adipocyte size, and subsequently, an elevation in serum NEFA levels.…”
Section: Discussionsupporting
confidence: 81%
“…As a result, the ethanol-fed rats exhibited increased liver/body weight ratios partly due to protein ( Kharbanda et al, 2007b ) and fat accumulation in the liver compared with respective controls ( Rasineni et al, 2014 ). The latter occurred as a result of the combined effect of alcohol-induced de novo lipogenesis and adipose-derived fatty acid uptake and esterification as well as decreased fatty acid oxidation and VLDL secretion ( Kharbanda et al, 2009 ; Rasineni et al, 2019a ). Fasting for 48 h caused a significant decrease in body weights of all experimental animals except HFD-fed rats, which is consistent with reports in the literature ( Li and Wassner, 1984 ).…”
Section: Discussionmentioning
confidence: 99%
“…[177][178][179] However, after chronic alcohol consumption higher serum ghrelin levels are reported in human drinkers and experimental animals. [180][181][182][183] Increased circulating ghrelin promotes ALD pathogenesis by slowing pancreatic insulin secretion, allowing adipose lipolysis to promote hepatic steatosis. 181,182 In addition to inhibiting insulin secretion, ghrelin directly promotes fat accumulation in hepatocytes by activating hepatic lipogenesis and increasing fatty acid transporters, while downregulating fatty acid oxidation.…”
Section: Potential New Therapies and Targets For Ald Treatmentmentioning
confidence: 99%
“…Rodent studies reveal that chronic alcohol administration significantly decreases circulating insulin levels [11] and glucose-stimulated insulin secretion from the pancreatic islets [12]. Studies have revealed that the alcohol-induced elevation of circulating ghrelin, a hormone mainly secreted from the stomach, inhibits insulin secretion from pancreatic β-cells [11,13]. In other experimental studies, rodents on a chronic alcohol diet show decreased pancreatic expression of glucokinase [5], glucose transporter-2 [5], and gamma-aminobutyric acid (GABA) receptors [14], all potential mechanisms for decreased insulin release.…”
Section: Chronic Alcohol Consumption Dysregulates Pancreatic Endocrinmentioning
confidence: 99%
“…Insulin is a critical hormone that regulates carbohydrate and lipid homeostasis. Several clinical and preclinical studies have revealed that alcohol consumption impairs basal and glucose-stimulated insulin secretion [6,[9][10][11][12] and mechanistic insights have also been documented [5,6,11,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%